PERAN AGAMA DALAM MEMBANGUN JIWA NASIONALISME SERTA EDUKASI LEMBAGA KEUANGAN SYARIAH DI ERA DIGITAL PADA MASYARAKAT - Rachman, Addif Zikri; Samarta, Cintya Putri; Hanani, Farrij Luthfiatul; Qolami, Hawa; Hardyansyah, Muhammad; Saifullah, Muhammad; Nabila, Mukfiyah Fuaydah; Deraya, Muthia Kamilla; Rizki, Rona Iyut; Aziz, Salsabela Afra; Az-Zahra, Siti Fatimah; Heri, Totong (LPPM Institut Pendidikan Nusantara Global, 2024)
Social Work Lectures (KKS) are a concrete manifestation of implementing the Tri Dharma of Higher Education, namely the service aspect. The theme of the Social Work Lecture (KKS) that the author uses is religious teaching and education about sharia financial institutions with program targets for RA Darul Fallah and TPQ An-Najah students, MI Nurut Taqwa, as well as the community in the student's neighborhood. The author designed several special programs related to the KKS theme. It is hoped that the programs that the author has designed can achieve the objectives of the chosen theme. The aim of this KKS activity is to strengthen and support the community's economy as well as improve the quality of Islamic Religious Education in Bojongrangkas Village in the form of community service by planning several collaborative activities between PAI, PBA and PS study programs in the form of Teaching FAI, Sharia Banking Socialization on Financial Planning, NOBAR (Watch together) about Islam with students, Blessed Friday Program, Competitions and Art Performances.